Exploring radio emissions from confirmed exoplanets using SKA - Fatemeh Bagheri; Fatemeh Bagheri; Anshuman Garga; Ramon E. Lopez (Frontiers in Astronomy and Space Sciences)
Our understanding of magnetic fields in exoplanets remains limited compared to those within our solar system. Planets with magnetic fields emit radio signals primarily due to the Electron Cyclotron Maser Instability mechanism. In this study, we explore the feasibility of detecting radio emissions from exoplanets using the Square Kilometre Array (SKA) radio telescope. Utilizing data from the NASA Exoplanet Archive, we compile information on confirmed exoplanets and estimate their radio emissions using the RBL model. Our analysis reveals that four exoplanets—Qatar-4 b, TOI-1278 b, CoRoT-10 b, and HAT-P-20 b—potentially exhibit radio signals suitable for observation with the SKA telescope.